Notes on Onciderini (Coleoptera, Cerambycidae, Lamiinae) - Monnê, Miguel A.; Fragoso, Sergio A. (Pesquisa Agropecuaria Brasileira, 2014)
The present note deals with Onciderini of the "Museu Nacional" collection, where all the holotypes are deposited. The following nomenclatural alterations are proposed: 1) Truncatoides Dillon & Dillon, 1945, is a n. syn. of Lesbates Dillon & Dillon, 1945. Lesbates hauffi Tippmann, 1953 is a n. syn. of Lesbates caviunas Dillon & Dillon, 1949 n. comb., and Lesbates axillaris Thomson, 1860 is a resulting n. comb. A key for identification of all species included presently in Lesbates is provided. 2) Neodillonia is a n. name for Dillonia Lane, 1955, preoccupied by Dillonia Haeckel, 1847 (Pisces), resulting in Neodillonia adspersa Laporte, 1840n.comb. and N. albisparsa Germar, 1824 n. comb. 3) Pseudobeta Zajciw 1972, as the first available name, should substitute Beta Dillon & Dillon 1945, preoccupied by Beta Saussure, 1855 (Hymenoptera). Pseudobeta quadrisignata Zajciw, 1972 is a n. syn of Pseudobeta doris Thomson, 1868 n. comb. 4) Leus piperella Dillon & Dillon, 1946 is a n. syn. of Leus ramuli Bates, 1865 n, comb. 5) Trestonia chevrolatii Buquet, 1859 is a n. syn. of Trestonia frontalis Erichson, 1847 n. comb. The following are described as new: Pseudobeta seabral n. sp,. Ischioderes bahiensis n. sp., Paratrachysomus huedepohli n. gen., n. sp. and Cydros melzeri n. sp. from Brazil and Trestonia turbula n. sp. from Peru and Brazil.